Screen for mitochondrial DNA copy number maintenance genes reveals essential role for ATP synthase. Issue 6 (25th June 2014) - Fukuoh, Atsushi; Cannino, Giuseppe; Gerards, Mike; Buckley, Suzanne; Kazancioglu, Selena; Scialo, Filippo; Lihavainen, Eero; Ribeiro, Andre; Dufour, Eric; Jacobs, Howard T
Abstract: The machinery of mitochondrial DNA (mtDNA) maintenance is only partially characterized and is of wide interest due to its involvement in disease. To identify novel components of this machinery, plus other cellular pathways required for mtDNA viability, we implemented a genome‐wide RNAi screen in Drosophila S2 cells, assaying for loss of fluorescence of mtDNA nucleoids stained with the DNA‐intercalating agent PicoGreen. In addition to previously characterized components of the mtDNA replication and transcription machineries, positives included many proteins of the cytosolic proteasome and ribosome (but not the mitoribosome), three proteins involved in vesicle transport, some other factors involved in mitochondrial biogenesis or nuclear gene expression, > 30 mainly uncharacterized proteins and most subunits of ATP synthase (but no other OXPHOS complex). ATP synthase knockdown precipitated a burst of mitochondrial ROS production, followed by copy number depletion involving increased mitochondrial turnover, not dependent on the canonical autophagy machinery. Our findings will inform future studies of the apparatus and regulation of mtDNA maintenance, and the role of mitochondrial bioenergetics and signaling in modulating mtDNA copy number. Synopsis: An RNAi screen for genes needed in mtDNA copy number maintenance in Drosophila yielded 97 positives, including previously characterized mtDNA maintenance proteins, subunits of the cytoribosome, proteasome, and ATP synthase. An RNAi screen for genes needed in mtDNA copy number maintenance in Drosophila yielded 97 positives. These included previously characterized components of the mtDNA maintenance machinery. Other major classes of positives were the cytoribosome, proteasome, and ATP synthase. ATP synthase deficiency results in increased ROS and activation of mitochondrial turnover by pathway(s) distinct from classical autophagy. Abstract : An RNAi screen for genes needed in mtDNA copy number maintenance in Drosophila yielded 97 positives, including previously characterized mtDNA maintenance proteins, subunits of the cytoribosome, proteasome, and ATP synthase.